Brane Solutions in Supergravity and the Near-Horizon Geometries - Adeifeoba, Ademola (My University, 2018)
This note represents a summary of a talk given at the 2018 Summer Mathematical Physics seminar, with focus on the physical and the mathematical concepts of the holography principle and large-N dualities. Here, we present an elementary overview of the p-brane solutions in supergravity, setting up a stage for a fairly broad topics on the AdS/CFT correspondence.
Supplemental Materials: https://osf.io/tn2bp/
Keywords: D-brane; Membrane model: p-brane; Supergravity